Analisis Kinerja Dinas Pengelolaan Keuangan Daerah Di Bidang Pendapatan Pada Kabupaten Gayo Lues - Ketike, Remang; Harahap, R. Hamdani; Siregar, Nina Siti Salmaniah (Universitas Medan Area, 2021)
Based on this background, the formulation of the problem is What is the performance of the Regional Financial Management Service in the Revenue Sector in Gayo Lues Regency. Barriers to the performance of the Regional Financial Management Service in the Revenue Sector in Gayo Lues Regency. The research objective was to analyze Performance of the Regional Financial Management Service in the Revenue Sector in Gayo Lues District. Obstacles to the performance of the Regional Financial Management Service in the Revenue Sector in Gayo Lues Regency. The research method used was descriptive with qualitative analysis. Data collection was obtained from interviews, documentation, and observations. The results of the study are DPKD productivity is quite productive. This can be seen from the availability of funds for each activity and program to increase PAD. (2) The quality of DPKD services in providing service information regarding PAD is of sufficient quality. This can be seen from the procedure in providing information in accordance with the established SOP. The responsiveness of DPKD both in providing services always maintains satisfaction from taxpayers who need registration services and tax deposits. The DPKD is less responsible, there is an implementation of tasks that are not in accordance with the procedure. The DPKD conducts a mechanism of accountability, vertically to the Gayo Lues Regency Government and to the community. While the suggestions from this study are (1) Good cooperation is needed in the management of PAD between all parties not only the authorities but the community. In the preparation of the APBD a budget for extension programs and outreach programs for the community and better infrastructure are proposed. Special training or education needs to be carried out for employees to increase employee capabilities in technical matters.